Whole-Genome Analysis Reveals That the Nucleoid Protein IHF Predominantly Binds to the Replication Origin oriC Specifically at the Time of Initiation - Kasho, Kazutoshi; Oshima, Taku; Chumsakul, Onuma; Nakamura, Kensuke; Fukamachi, Kazuki; Katayama, Tsutomu (Frontiers in Microbiology, 2021)
The structure and function of bacterial chromosomes are dynamically regulated by a wide variety of nucleoid-associated proteins (NAPs) and DNA superstructures, such as DNA supercoiling. In Escherichia coli, integration host factor (IHF), a NAP, binds to specific transcription promoters and regulatory DNA elements of DNA replication such as the replication origin oriC: binding to these elements depends on the cell cycle but underlying mechanisms are unknown. In this study, we combined GeF-seq (genome footprinting with high-throughput sequencing) with synchronization of the E. coli cell cycle to determine the genome-wide, cell cycle-dependent binding of IHF with base-pair resolution. The GeF-seq results in this study were qualified enough to analyze genomic IHF binding sites (e.g. oriC and the transcriptional promoters of ilvG and osmY) except some of the known sites. Unexpectedly, we found that before replication initiation, oriC was a predominant site for stable IHF binding, whereas all other loci exhibited reduced IHF binding. To reveal the specific mechanism of stable oriC–IHF binding, we inserted a truncated oriC sequence in the terC (replication terminus) locus of the genome. Before replication initiation, stable IHF binding was detected even at this additional oriC site, dependent on the specific DnaA-binding sequence DnaA box R1 within the site. DnaA oligomers formed on oriC might protect the oriC–IHF complex from IHF dissociation. After replication initiation, IHF rapidly dissociated from oriC, and IHF binding to other sites was sustained or stimulated. In addition, we identified a novel locus associated with cell cycle-dependent IHF binding. These findings provide mechanistic insight into IHF binding and dissociation in the genome.